2012
DOI: 10.1007/s11665-012-0308-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Study of Ti-12V-9Sn Shape Memory Alloy with C.P. Ti and Ti-12V Alloy for Potential Biomedical Application

Abstract: The microstructure, mechanical properties, and electrochemical behavior of Ti-12V-9Sn shape memory alloy were investigated, with commercial pure titanium (C.P. Ti) and Ti-12V alloy as controls. The metastable b phase was partially retained and a¢¢ martensite phase was obtained in Ti-12V-9Sn alloy, whereas only martensitic phases (a¢ and a¢¢) existed in Ti-12V alloy at room temperature. Ti-12V-9Sn alloy exhibited a good combination of strength and elongation, which showed a ''double yield'' feature, along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The improvement of micro-hardness of Ti-V-Al shape memory alloys with Sn addition can be attributed to the grain refinement and solid solution strengthening. The maximum microhardness of 339.4 HV can be attained in Ti-V-Al shape memory alloys by optimizing 5.0 at.% Sn, which is larger than that (311 HV) of the reported Ti-V-Sn shape memory alloy [47]. The higher micro-hardness of Ti-V-Al-Sn shape memory alloy can be attributed to the grain refinement and solution strengthening of the soluble Al in matrix.…”
Section: Mechanical and Functional Propertiesmentioning
confidence: 75%
See 1 more Smart Citation
“…The improvement of micro-hardness of Ti-V-Al shape memory alloys with Sn addition can be attributed to the grain refinement and solid solution strengthening. The maximum microhardness of 339.4 HV can be attained in Ti-V-Al shape memory alloys by optimizing 5.0 at.% Sn, which is larger than that (311 HV) of the reported Ti-V-Sn shape memory alloy [47]. The higher micro-hardness of Ti-V-Al-Sn shape memory alloy can be attributed to the grain refinement and solution strengthening of the soluble Al in matrix.…”
Section: Mechanical and Functional Propertiesmentioning
confidence: 75%
“…When the Sn content increases, the maximum fracture strength of the present Ti-V-Al shape memory alloys continuously decreases from 962 to 792 MPa. Similarly, the Sn addition results in reduction in the maximum fracture strength of Ti-V shape memory alloy [47]. Nevertheless, the fracture strength of Ti-V-Al shape memory alloys with moderate Sn content is significantly higher than that of the reported Ti-V-Al-X (X = Fe, Co, Gd, etc.)…”
Section: Mechanical and Functional Propertiesmentioning
confidence: 89%
“…Many reported that the addition of Sn is benefit to the formation of passive film of Ti-based Alloy with high corrosion resistance, e.g. Ti–Cu [15], Ti–Ta [22], Ti–V [29] and Ti 60 Zr 10 Ta 15 Si 15 [21] alloys. The evidence presented in Figure 4 confirms that the addition of Sn is helpful to increase the resistance of the passive film of Ti7Cu x Sn alloy in 0.9 wt-% NaCl solution.…”
Section: Resultsmentioning
confidence: 99%